2016
DOI: 10.4039/tce.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Complex ecological relationships among an assemblage of indigenous hymenopteran parasitoids, the exotic European woodwasp (Sirex noctilio; Hymenoptera: Siricidae), and a native congener

Abstract: We collected naturally infested Pinus resinosa Aiton (Pinaceae) and P. sylvestris Linnaeus to investigate phenological patterns and quantify parasitism by a suite of native hymenopteran parasitoids on two woodwasps (Hymenoptera: Siricidae): the invading non-native European woodwasp, Sirex noctilio Fabricius, and a co-colonising native, S. nigricornis Fabricius. We sampled a total of 76 trees from two field sites in 2010 and seven sites in 2011. In raw abundance, S. noctilio outnumbered S. nigricornis by 2:1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…For example, rhyssine parasitism was positively correlated with S. noctilio density in individual logs, but I. l. ensiger parasitism was not. Previous studies in North America have consistently found parasitism by I. l. ensiger and rhyssines to be 15–25% (Eager et al ., ; Ryan et al ., ; Foelker et al ., ), but with considerable variability among individual trees and collectively less than parasitism in the Southern Hemisphere (35–40%) (Cameron, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, rhyssine parasitism was positively correlated with S. noctilio density in individual logs, but I. l. ensiger parasitism was not. Previous studies in North America have consistently found parasitism by I. l. ensiger and rhyssines to be 15–25% (Eager et al ., ; Ryan et al ., ; Foelker et al ., ), but with considerable variability among individual trees and collectively less than parasitism in the Southern Hemisphere (35–40%) (Cameron, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sirex noctilio Fabricius (Hymenoptera: Siricidae) is a pest of pine plantations in the Southern Hemisphere and a recent invader to eastern North America (Hoebeke et al ., ; Slippers et al ., ). Although populations have not reached outbreak levels, it has quickly become the most abundant woodwasp colonising pine in northeastern North America (Eager et al ., ; Standley et al ., ; Ryan et al ., ; Foelker et al ., ). Female woodwasps inoculate host trees with a phytotoxic mucus and mutualist fungus, Amylostereum areolatum (Fr.)…”
Section: Introductionmentioning
confidence: 97%
“…In northeastern North America S. noctilio is now the most abundant woodwasp attacking pines (Long et al 2009;Ryan et al 2012a;Foelker et al 2016). Unfortunately, there are no records of the population densities or tree use by S. nigricornis before S. noctilio arrived but now, use of suppressed pines by S. nigricornis is much less than use of this resource by S. noctilio (e.g., Table 2).…”
Section: Comparing Abundance Of Sirex Speciesmentioning
confidence: 99%
“…Sirex nigricornis can co-occur in pines with S. noctilio (Ryan et al 2012a;Hajek et al 2013). Most adults of S. nigricornis emerge to mate and oviposit approximately 1-2 months after S. noctilio (Ryan et al 2012a;Foelker et al 2016;Suppl. material 1: B).…”
Section: Introductionmentioning
confidence: 99%
“…banksiana , or P . strobus [6, 7, 34, 35], although none of those studies compared all four pine species at once. In a study where co-occurring P .…”
Section: Introductionmentioning
confidence: 99%